1982
DOI: 10.1073/pnas.79.13.3954
|View full text |Cite
|
Sign up to set email alerts
|

Nonoxidative ethanol metabolism: formation of fatty acid ethyl esters by cholesterol esterase.

Abstract: The recent identification of myocardial metabolites ofethanol-fatty acid ethyl esters-suggests that some ofthe pathophysiological derangements associated with alcohol-induced heart muscle disease may be a consequence ofproducts ofmyocardial ethanol metabolism. The donor of the fatty acid moiety in the formation offatty acid ethyl esters has been identified as nonesterified fatty acid. Fatty acid esterification with ethanol is shown to be mediated by cholesterol esterase (sterol-ester acylhydrolase, EC 3.1.1.13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 30 publications
0
48
0
Order By: Relevance
“…11,12 Pancreatic homogenates were also noted to have an ability to synthesize FAEEs from FAs and ethanol,20,23 and the putative enzyme for this was thought to be a lipase. 24,25 It has been shown that the FAEE synthase activity of the putative enzyme exceeds its lipolytic capacity by several fold. 25 Triglyceride (TG) forms >80% of the adipocyte mass, 26e28 oleic acid (OA) being the most enriched FA.…”
mentioning
confidence: 99%
“…11,12 Pancreatic homogenates were also noted to have an ability to synthesize FAEEs from FAs and ethanol,20,23 and the putative enzyme for this was thought to be a lipase. 24,25 It has been shown that the FAEE synthase activity of the putative enzyme exceeds its lipolytic capacity by several fold. 25 Triglyceride (TG) forms >80% of the adipocyte mass, 26e28 oleic acid (OA) being the most enriched FA.…”
mentioning
confidence: 99%
“…FAEE of predominantly ethyl palmitate (2.7-3.7 nmol/g tissue), ethyl stearate (4.0-5.5 nmol/g tissue), and ethyl oleate (2.1-2.7 nmol/g tissue) could be detected. 7 placenta. The presence of FAEE synthase in placenta on gestational d 7 with resultant FAEE accumulation and persistence of FAEE for at least 7 d was suggested by the following experiment.…”
Section: Retention Timementioning
confidence: 99%
“…Nonoxidative metabolism of ethanol to FAEE occurs in both liver and extrahepatic tissues (7) and is catalyzed by FAEE synthases. These lipids have been shown to bind to mitochondria in intact cells and to uncouple oxidative phosphorylation in mitochondrial preparations in vivo (8).…”
mentioning
confidence: 99%
“…Porcine pCEase was purchased from Worthington Biochemical Corp. (Freehold, NJ, USA) and dissolved in the same Tris buffer. CEase activities in various sources were determined by hydrolysis of cholesteryl-14C-oleate to cholesterol and 14C -oleic acid (10)(11)(12) . The reaction mixture (total volume of 0.2 ml) consisting of L-a-lysophosphatidylcholine, cholesteryl-14C-oleate, enzyme protein, DMSO containing the dissolved test compound, 0.1 M Tris-HC1 buffer (pH 7.5, nCEase; pH 7.0, pCEase) or 0.1 M acetic buffer (pH 4.5, aCEase) and saline was incubated for 1 hr at 371C (duplicate or triplicate assays).…”
Section: Hmg-coa Reductase Assaymentioning
confidence: 99%